Effects of Sorghum Cookies (Sorghum Bicolor L. Moench) on Fasting Glucose, Triglyceride, High-Density Lipoprotein level, and Body Fat Percentage in Adolescent Obesity - Latifah Rachmawati; Maria Mexitalia; Muflihatul Muniroh; Diana Nur Afifah; Adriyan Pramono (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2022)
Background: Adolescent obesity is related to the risk of metabolic syndrome. Several studies have proven the effect of dietary interventions on metabolic parameters in obese individuals. A source of complex carbohydrates that is still rarely developed in the obese diet is sorghum which contains resistant starch.Objective: The study was to reveal the effect of sorghum cookies on Fasting Glucose (FG), Triglycerides (TG), High-Density Lipoprotein (HDL), and Body Fat Percentage (BFP) in obese adolescents.Materials and Methods: This quasi-experiment with the pre-post control-group design was conducted on 20 boys and 20 girls (divided into 10-boy control group, 10-girl control group, 10-girl intervention group, and 10-girls intervention group) with the age range of 13–15 years who attended Junior High School 14 Semarang chosen by consecutive sampling. Weight, Height, and BFP were measured directly by BIA. Metabolic parameters (FG, TG, and HDL levels) were taken through venous and 10-hour fasting. Energy intake and physical activity were taken by interview using the food recall questionnaire for 6 days randomly and IPAQ. The intervention of sorghum cookies was given in 90 grams/day with 473 kcal/day for 28 days. The analysis of the effect of the intervention was conducted by a paired t-test and independent t-test.Results: At 28-days sorghum cookies intervention resulted in lower levels of FG, TG, and BFP in the intervention boy group (p < 0.05) and BFP in the girl group (p < 0.05). The intervention of sorghum cookies showed no effect on HDL levels in boys, and it did not affect FG, TG, or HDL levels of the girl subjects (p > 0.05). Conclusion: Obese adolescents who had been receiving intervention of 90 grams of sorghum cookies for 28 days appeared to have lower levels of fasting glucose, triglycerides, and body fat percentage.